ANALISIS IMPLEMENTASI ASESMEN DALAM KURIKULUM MERDEKA DI SDN MINTARAGEN 4 KOTA TEGAL - Calis Meila Intantri; Ellianawati, Barokah Isdaryanti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The transformation of education in Indonesia through the Merdeka Curriculum reflects a paradigm shift from results-oriented learning to a process-centered and student development-focused approach. In this context, assessment is no longer merely an endpoint measurement tool but an integral part of the formative, diagnostic, and reflective learning process. This study aims to analyze the implementation of assessment within the Merdeka Curriculum at SDN Mintaragen 4 Kota Tegal. The primary focus lies on the forms, strategies, and challenges of assessment practices carried out by teachers in the learning process. Employing a descriptive qualitative approach, data were collected through classroom observations, in-depth interviews, and document analysis. The results indicate that assessments in the Merdeka Curriculum emphasize continuous formative assessment, allowing students to reflect on their learning processes and outcomes, while also enhancing learning quality. However, several challenges were found, including limited teacher understanding of formative assessment principles and time constraints that hinder optimal implementation. This article recommends strengthening teacher training and developing a culture of reflection as key strategies for successful assessment practices in the Merdeka Curriculum.